Design and Build Internet of Things Smart Home For Android Based Electronic Equipment Management System - Dwi Iskandar; Canggih Ajika Pamungkas; Norma Puspitasari; Muh Alif Fathoni (ISB Atma Luhur, 2022)
Energy consumption apart from the use of low-power consumption devices, it is also necessary to use energy-saving behavior that supports sustainable energy. Unwise use of electricity will of course have an impact on the high use of electricity, this also affects the depletion of electrical energy supplies because the need for electrical energy is greater than the supply of electrical energy, for that it is hoped that every community understands the efforts to use electricity wisely. Problems faced by households in managing the use of electrical energy include: Not using LED lights (Light Emitting Diodes); Using unnecessary electronic equipment; It is not wise to use equipment that requires electrical energy. The purpose of this research, among others, is how to monitor the use of electrical energy in the household by utilizing IoT and connected to the Android application to make monitoring easier. The contribution given by the researcher is how to combine microcontroller hardware, internet and android applications so that they can support the use of smart homes at home. Research Methodology includes data collection, needs analysis, program development, tool design, testing. Conclusions that can be drawn based on research that has been done include: Smart home that has been made can help turn on and turn off electronic equipment at home, Smart home applications that are made can be connected to the internet network, Smart Home applications can be installed on Smartphones with operating systems Android versions Android 7.0 – 7.1 (Nougat), Android 8.0 – 8.1 (Oreo), Android 9 (Pie), Android 10 (Android Q). For the implementation of using the application, the user must prepare the IoT Smarthome Hardware that has been designed and then connected to the internet. If so, household electronic equipment can be accessed via Android Mobile. In working on the Internet of Things Smart Home For Android, the author follows the path of the Research Methodology.